2021
DOI: 10.1177/23969873211010069
|View full text |Cite
|
Sign up to set email alerts
|

Serum GFAP for stroke diagnosis in regions with limited access to brain imaging (BE FAST India)

Abstract: Introduction Despite a high burden of stroke, access to rapid brain imaging is limited in many middle- and low-income countries. Previous studies have described the astroglial protein GFAP (glial fibrillary acidic protein) as a biomarker of intracerebral hemorrhage. The aim of this study was to test the diagnostic accuracy of GFAP for ruling out intracranial hemorrhage in a prospective cohort of Indian stroke patients. Patients and methods This study was conducted in an Indian tertiary hospital (Christian Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have highlighted the potential of blood-derived parameters as biomarkers for timely patient triage, therapeutics, and stroke mechanisms [ 30 , 31 , 32 ]. Easily accessible fluid biomarkers can provide an objective evaluation of the real-time panorama, supporting stroke diagnosis or predicting the patients’ outcome and ultimately guiding clinical decisions [ 20 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the potential of blood-derived parameters as biomarkers for timely patient triage, therapeutics, and stroke mechanisms [ 30 , 31 , 32 ]. Easily accessible fluid biomarkers can provide an objective evaluation of the real-time panorama, supporting stroke diagnosis or predicting the patients’ outcome and ultimately guiding clinical decisions [ 20 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also analyzed serum GFAP (sGFAP) in patients with acute stroke and consistently indicated that sGFAP, measured in the hyperacute phase, is substantially higher in intracerebral hemorrhage compared to ischemic stroke [ 3 5 ]. In addition, higher sGFAP levels on day one after the onset of ischemic stroke have been associated with worse functional neurological outcome at one year even after adjusting for age, initial clinical stroke severity and infarct size [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blood GFAP levels increase not only in NMOSD but in various neurological diseases ( 109 ), thus the specificity of GFAP as an NMOSD biomarker should be discussed. Blood GFAP levels in patients with NMOSD, which often increase more than 1,000 pg/mL during relapses, tend to be higher than in patients with other diseases such as relapsing remitting MS ( 59 , 60 , 77 ), progressive MS ( 59 61 ), and even ischemic stroke ( 62 ). This is because patients with NMOSD are accompanied by direct damage of astrocytes.…”
Section: Special Considerationsmentioning
confidence: 92%